2017
DOI: 10.1101/131003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular mapping ofYrTZ2, a stripe rust resistance gene in wild emmer accession TZ-2 and its comparative analyses withAegilops tauschii

Abstract: The genetic and comparative maps of YrTZ2 provide framework for map-based 22 peer-reviewed) is the author/funder. All rights reserved. No reuse allowed without permission.The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/131003 doi: bioRxiv preprint first posted online Apr. 26, 2017; 3 cloning and marker-assisted selection (MAS) of YrTZ2.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…5, Table S3). Thus, other genes reported to be located on 1BS chromosome, especially these originating from WEW, such as YrSM139-1B (Zhang et al , 2016) and YrTz2 (Wang et al , 2018), should be tested for allelism/identity to Wtk1 .…”
Section: Discussionmentioning
confidence: 99%
“…5, Table S3). Thus, other genes reported to be located on 1BS chromosome, especially these originating from WEW, such as YrSM139-1B (Zhang et al , 2016) and YrTz2 (Wang et al , 2018), should be tested for allelism/identity to Wtk1 .…”
Section: Discussionmentioning
confidence: 99%
“…Wild emmer wheat accession IW2 was also resistant to stripe rust (Wang et al ., 2018). Sequence amplification revealed that IW2 also contains the broad‐spectrum stripe rust resistance gene Yr15 .…”
Section: Discussionmentioning
confidence: 99%
“…A. tauschii is the ancestor of the D genome in wheat and it was previously shown to encode resistance to powdery mildew (Majka et al, 2017), stem rust (Periyannan et al, 2013), leaf rust (Mohler et al, 2019), stripe rust (Wang et al, 2018), andSTB (McKendry &Henke, 1994). The latter study highlighted both qualitative and quantitative resistance among A. tauschii lines to STB disease, some of which exhibited isolate-specific resistance.…”
Section: Discussionmentioning
confidence: 99%